METHODOLOGY OF DEVELOPING READING COMPETENCE THROUGH LITERARY TEXTS IN HIGHER EDUCATION - Aliqulova Feruza O‘ktam qizi; Murtazinova Zebo Oromiddin qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study investigates the methodology of developing reading competence through literary texts in higher education, with particular emphasis on the pedagogical value of literature in foreign language and literacy instruction. Literary texts provide students with authentic language input, cultural awareness, and opportunities for critical interpretation. The research explores how the integration of novels, short stories, poems, and other literary genres contributes to the improvement of reading comprehension, vocabulary acquisition, analytical thinking, and emotional intelligence. Special attention is given to interactive and student-centered teaching approaches, including discussion-based learning, reflective reading, and interpretative analysis. The findings reveal that literary-based instruction significantly increases students’ cognitive involvement, motivation, and emotional engagement during the learning process. Moreover, exposure to literary works enhances empathy, creativity, and the ability to understand diverse perspectives and cultural contexts. The study concludes that the effective use of literary texts in higher education plays an important role in fostering advanced reading competence and developing students’ overall communicative and intellectual abilities.